2014
DOI: 10.5771/0935-9915-2014-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Does alignment elicit competency-based HRM? A systematic review

Abstract: Does alignment elicit competency-based HRM?A systematic review ** Internationally, human resource practice is committed to competency-based HRM. HR practitioners and management consultants expect the outcomes of competencybased HRM to include improved employee and organizational performance. However, research indicates that a commitment to the use of competency-based HRM does not automatically guarantee these outcomes. Therefore, HR practitioners have called for academic work to enhance our understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 56 publications
0
37
0
2
Order By: Relevance
“…The complexity and unpredictability of events in extreme environments require the development of competences to occur during the job. This situation increases the need for two-way communication to obtain the best strategic approach for future team effectiveness (Audenaert, Vanderstraeten, Buyens, & Desmidt, 2014;Lindgren, Henfridsson, & Schultze, 2004). Additionally, the physical distance between the team leader and the team is often high in extreme environments (Dalenberg, Vogelaar, & Beersma, 2009;Hannah et al, 2009), diminishing the team leader's ability to provide an appropriate direction to its team (Hannah et al, 2009).…”
Section: Two-way Communication During the Performance Management Prmentioning
confidence: 99%
“…The complexity and unpredictability of events in extreme environments require the development of competences to occur during the job. This situation increases the need for two-way communication to obtain the best strategic approach for future team effectiveness (Audenaert, Vanderstraeten, Buyens, & Desmidt, 2014;Lindgren, Henfridsson, & Schultze, 2004). Additionally, the physical distance between the team leader and the team is often high in extreme environments (Dalenberg, Vogelaar, & Beersma, 2009;Hannah et al, 2009), diminishing the team leader's ability to provide an appropriate direction to its team (Hannah et al, 2009).…”
Section: Two-way Communication During the Performance Management Prmentioning
confidence: 99%
“…Whereas Malaysian food industries' requirement is to improve the employee competency to highlight the obstacles involved in enhancing the employee competency, it is necessary for the Malaysian organizations in bringing about the sustainability of all kind of businesses. The last two decades have evidenced a majority of organizations using employee competency to sustain the performance of organizations (Audenaert et al, 2014;Campion et al, 2011). Adnan et al (2011) indicated that employee competency played a significant effect on Malaysian firms' performance.…”
Section: Introductionmentioning
confidence: 99%
“…A job analysis produces a job description or job specification, which specifies what is required for effective performance (Audenaert, et al 2014). But a competency model shows the way to achieve that effective performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Job analysis and competency models can coexist in an organization (Bonder, Bouchard and Bellemare 2011). Competency models can have two linkages; vertical linkage in which a competency model is linked to the strategies of the organization and an internal linkage in which the competency model is linked to the HR practices (Audenaert, et al 2014). Such linkages may not be clear always and hence linkage ambiguity can exist.…”
Section: Literature Reviewmentioning
confidence: 99%